Dialectics Islamic Inheritance Law and Law of Indigenous Heritage - Suhairi, Suhairi (Opción, 2019)
Paksi Pak Skala Brak Indigenous Lampung is a community that previously adhered to the teachings of Hinduism, and then converted to the teachings of Islam, even the whole is Muslim, but on the other hand, has customary law. So it is interesting to study the dialectics of Islamic inheritance law and Skala Brak Lampung customary inheritance law. The purpose of this study is: To elaborate on the dialectics of Islamic inheritance law and customary inher- itance law in the Skala Brak Indigenous Lampung. The results of this study indicate the Skala Brak Lampung indigenous people are quite strong in im- plementing the provisions of customary law, including customary inheritance law. But on the other hand, there was a shift for the indigenous people of Lam- pung are already highly educated and a good Islamic outlook, especially the ones who do not live anymore in Skala Brak or studying outside of Lampung. For those who are, doing the distribution of inheritance in accordance with the provisions of Islamic inheritance even if it does not follow the provisions of Islamic inheritance in full, giving part of the inheritance for girls? This happens due to the strengthening of understanding and practice of Islamic teachings, as a form of dialectic Islamic inheritance law and customary inher- itance law of Lampung.